A numerical investigation in characteristics of flow force under cavitation state inside the water hydraulic poppet valves. (August 2017) - Han, Mingxing; Liu, Yinshui; Wu, Defa; Zhao, Xufeng; Tan, Huaijiang
Highlights: The flow field characteristics in water hydraulic poppet valves has been analyzed. The flow force under cavitation state in poppet valves is investigated. The effects of geometric parameters on flow characteristics have been studied. The effects on cavitation and flow force by backpressure have been analyzed. Abstract: Compared with the oil hydraulic systems, cavitation is more serious in water hydraulic systems due to the higher saturated vapor pressure of water. Poppet valve is one of important hydraulic components and cavitation is easy to happen due to the sharp pressure drop caused by throttling. This paper presents a numerical investigation into the flow force and cavitation characteristics inside water hydraulic poppet valves. Three kinds of typical structures of poppet valves are selected in the research. The effects of geometric parameters and backpressure of the poppet valves on flow characteristics, cavitation and flow force have been analyzed. Considering the axisymmetric structure of the valves, a half of 2D mixture model is selected and a two-phase mixture model is adopted in the calculation. The accuracy of the numerical models has been validated by comparing the simulation results with the experiment data. The results reveal that two-stage throttle valve (TS valve) can effectively suppress the occurrence of cavitation while the flow force of TS valve is much bigger than that of other valves. By comparing the simulation results under two different boundary conditions (including with backpressure and without backpressure), it seems that cavitation could slightly decrease the flow force.